ANALISIS BAURAN PEMASARAN PADA HOME INDUSTRI WADAI KELEMBEN DESA TAMBAK ANYAR MARTAPURA - Malihah, Lola (Universitas Borneo Tarakan, 2023)
This study aims to analyze the marketing strategy carried out by Home Industry Wadai Kelamben business actors in Tambak Anyar Martapura Village. Home Industry is one of the community's efforts in improving the economy. Home Industri Wadai Kelamben has an interesting marketing strategy to be further researched considering that this business is able to survive in the midst of current economic competition conditions. This research is a field research with a qualitative descriptive approach. The subjects in this study are business owners and employees of Home Industri Wadai Kelamben while the object is the marketing strategy applied. Data collection techniques use observation, interview and documentation methods. The data analysis used is data reduction, triangulation and drawing conclusions. The results obtained from this study are: Food products offered are of high quality. The price offered is relatively cheap and affordable for all consumers. The place chosen as a strategic selling location and easy to reach consumers, because it is on the main road across districts and across provinces. Business actors have also promoted by advertising products through social media and the most supportive is word of mouth carried out by consumers who have purchased. This shows the quality of the product so that consumers become satisfied and loyal. From the Islamic economic side, the marketing strategy carried out is also not contrary to Islamic muamalah.Â